Mapeamento da herdabilidade regional da resistência ao Colletotrichum lindemuthianum em feijão-comum - Cabral, James Frank Mendes (2024)
This study addresses the complexity of anthracnose, a devastating disease affecting common beans, and the challenges faced in genetic research. The genetic variability of the pathogen responsible for anthracnose, Colletotrichum lindemuthianum, makes the identification of resistance genes a challenging task due to the polygenic nature of this trait. However, notable advances are occurring in genetic research, with emphasis on genomics and the use of molecular markers. These techniques have played a fundamental role in the search for resistance to anthracnose. The study discusses the use of advanced genome-wide association techniques to identify anthracnose resistance genes. These advances are accelerating the process of genetic improvement of beans, resulting in the development of more resistant and productive cultivars. This contributes to global food security, as beans are an important grain in the diets of many populations. The study also highlights the importance of genetic research in identifying new sources of resistance to anthracnose and understanding the complex genetic interactions involved in this disease. This information is valuable for plant genetic improvement and to ensure sustainable bean production worldwide. Furthermore, the study presents the results of an experiment that used regional heritability mapping to identify new sources of resistance to anthracnose in different races of the pathogen. 12 quantitative trait loci distributed across chromosomes Pv01, Pv02, Pv04, Pv08 and Pv11 were identified, demonstrating the effectiveness of this approach in identifying genes of interest. In summary, genetic research is playing a crucial role in combating anthracnose and finding lasting solutions to this disease. Advances in genomics and the use of molecular markers are accelerating the development of new, more resistant and productive common bean cultivars, contributing to global food security.